Breaking the silence: Examining process of cyber sextortion and victims’ coping strategies - Wang, Fangzhou (International review of victimology, 2025)
Sextortion is the threat to distribute intimate, sexual materials unless a victim complies with particular demands. Cyber sextortion, specifically, takes advantage of the Internet’s anonymous nature and uses explicit personal images to inflict harm on victims. Despite this crime’s serious nature, there is a dearth of empirical knowledge of sextortion, particularly the process of fear management for the victims. This article employed a qualitative content analysis of the victim testimonials posted on the Reddit sextortion forum to explore the coping mechanisms of 175 cyber sextortion victims. Borrowed from the transactional model of stress and coping developed by Lazarus and Folkman, the characteristics of person–environment stimuli, ransom, appraisal and coping, revisit, and reappraisal were identified and revealed an extended model of fear and stress management applied particularly among sextortion victims. In addition, characteristics that are unique to female and male victims are also revealed in this analysis. In sum, the dynamic nature of fear and stress management among victims of sextortion implies specific crime control and prevention policies.